High sensitivity and fast response optical fiber nucleic acid sensor. (October 2022) - Shen, Changyu; Chen, Xiaoman; Huang, Zhenlin; Wang, Zhihao; Liu, Jiaxiang; Deng, Huitong; Liu, Dejun; Shu, Fangzhou
Highlight: A label-free, high sensitivity and fast response nucleic acid (NA) sensor was presented. The single-stranded probe NA with known sequence was fixed on the optical fiber Mach-Zehnder interferometer (MZI) surface by covalent fixation method. And the complementary target NA could be detected through the changing of the spectra of the MZI. Thanks to the high sensitivity of MZI and the high fixation efficiency of covalent fixation method, the optical fiber NA sensor showed a fast response of 30 s and a high sensitivity of 0.175 dB/nM with a minimum detection concentration of 1 nM, which provided a new possibility for the NA detection. Abstract: A label-free optical fiber Mach-Zehnder interferometer (MZI) based biosensor was proposed for the specificity detection of single-stranded nucleic acid (NA). The MZI was made of a fiber sandwich structure by a core-offset fusion splicing means. The piranha solution, APTES (3-Aminopropyltriethoxylsilan) and GA (Glutaraldehyde) were used for the chemical modification of the optical fiber surface, and then the single-stranded probe NA with the known sequence was fixed on the optical fiber surface by covalent fixation method. The specificity of complementary target NA could be detected through the changing of the spectra of the MZI. Thanks to the high sensitivity of the MZI and the high fixation efficiency of the covalent fixation method, the optical fiber MZI based NA sensor showed a fast response of 30 s and a high sensitivity of 0.175 dB/nM with a minimum detection concentration of 1 nM.